Trends in Opioid and Non-opioid Prescriptions in Austria (2016–2021): A Nationwide Study on Utilization and Concomitant Benzodiazepine Use - Aylin Bilir; Lorenz Kapral; Andrea Michalek-Sauberer; Razvan Bologheanu; Felix Gruber; Oliver Kimberger (Pain and Therapy)
Abstract Introduction Although global opioid consumption is decreasing, high-income populations are experiencing an increase. Data on specific opioid-prescribed and at-risk patient groups in Austria are lacking. Methods We performed a retrospective observational population-based study analysing health insurance data between January 2016 and December 2021. The dataset included demographic information; hospital data, including coded primary and secondary discharge diagnoses; and prescription data for all legally available opioids and nonopioid analgesics. The primary objective was to describe trends in opioid and nonopioid analgesic prescriptions. Logistic regression analysis was conducted to identify potential risk factors for receiving an opioid prescription. Results The study cohort included 7,274,651 individuals. During the observation period, the percentage of individuals receiving an opioid prescription decreased by 14.69% (4.22–3.60%). The number of individuals receiving an opioid prescription was consistently greatest for tramadol. A particularly strong positive correlation was observed between opioid prescriptions and the concurrent use of benzodiazepines (odds ratio [OR], 1.45 [95% confidence interval CI, 1.43–1.47]). Furthermore, a history of persistent somatoform pain disorder (OR, 1.28 [95% CI, 1.21–1.36]) and a diagnosis of pain disorder (OR, 1.26 [95% CI, 1.25–1.28]) were identified as significant risk factors. In 2021, general practitioners were the predominant initial opioid prescribers, issuing 82.17% of the prescriptions, followed by hospital staff and orthopaedic specialists. Conclusion Prescription opioid use decreased from 2016 to 2021, with tramadol representing the most prevalent opioid. The study revealed a strong link between opioid and benzodiazepine prescriptions and an association with persistent somatoform pain disorder, where opioid use is typically not recommended. Interactive map available for this article.